Hierarchical self-assembly into chiral nanostructures. Issue 3 (6th December 2021) - Sang, Yutao; Liu, Minghua
Abstract : This review shows how chirality may be used for the design, construction and evolution of higher ordered and complex chiral nanostructures through hierarchical self-assembly. Abstract : One basic principle regulating self-assembly is associated with the asymmetry of constituent building blocks or packing models. Using asymmetry to manipulate molecular-level devices and hierarchical functional materials is a promising topic in materials sciences and supramolecular chemistry. Here, exemplified by recent major achievements in chiral hierarchical self-assembly, we show how chirality may be utilized in the design, construction and evolution of highly ordered and complex chiral nanostructures. We focus on how unique functions can be developed by the exploitation of chiral nanostructures instead of single basic units. Our perspective on the future prospects of chiral nanostructures via the hierarchical self-assembly strategy is also discussed.